2001
DOI: 10.3171/foc.2001.11.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Terson's syndrome in subarachnoid hemorrhage and severe brain injury accompanied by acutely raised intracranial pressure

Abstract: Object The syndrome of retinal or vitreous hemorrhage in association with subarachnoid hemorrhage (SAH) is known as Terson's syndrome. The authors' purpose was to determine whether intraocular hemorrhage occurs with similar incidence when caused by severe brain injury accompanied by acutely raised intracranial pressure (ICP). Methods Prospective ophthalmological examination was performed in 22 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 19 publications
0
44
0
3
Order By: Relevance
“…In these studies, incidences of vitreous hemorrhages of 8 and 27.3% were reported, respectively [5,6,9]. For all ocular hemorrhages frequencies of 17, 18, 27, 46, and 16.7% were observed [5,6,9,12,13]. In our series, only 5% (n=4) of patients suffered from intravitreal hemorrhages, three underwent vitrectomy, and 28% suffered from intraretinal hemorrhages.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…In these studies, incidences of vitreous hemorrhages of 8 and 27.3% were reported, respectively [5,6,9]. For all ocular hemorrhages frequencies of 17, 18, 27, 46, and 16.7% were observed [5,6,9,12,13]. In our series, only 5% (n=4) of patients suffered from intravitreal hemorrhages, three underwent vitrectomy, and 28% suffered from intraretinal hemorrhages.…”
Section: Discussionmentioning
confidence: 50%
“…In pathological studies [17] and also retrospective studies [3], intraocular involvement is reported to be related to the severity of the clinical symptoms. Also, the relationship between intracerebral pressure as a marker of the severity of SAH and Terson's syndrome is well known [12]. Patients with higher Hunt-Hess grades exhibited statistically a higher frequency of intraocular involvement.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The results of our study agree with clinical observations and studies that increased brain pressure can be associated with retinal hemorrhages. In the case of an acute subarachnoidal hemorrhage with a marked increase in intracranial pressure, retinal hemorrhages and an intravitreal bleeding can develop as part of Terson's syndrome [18,19]. In other neurological disorders associated with brain edema and increased brain pressure such as mountain sickness, retinal hemorrhages can typically occur [20].…”
Section: Discussionmentioning
confidence: 99%